The algebraic diagrammatic construction scheme for the polarization propagator for the calculation of excited states - Dreuw, Andreas; Wormit, Michael (Wiley interdisciplinary reviews. Computational Molecular Science, 2015)
The algebraic diagrammatic construction (ADC) scheme for the polarization propagator provides a series of ab initio methods for the calculation of excited states based on perturbation theory. In recent years, the second‐order ADC(2) scheme has attracted attention in the computational chemistry community because of its reliable accuracy and reasonable computational effort in the calculation of predominantly singly excited states.